Postoperative Corneal and Surgically Induced Astigmatism following Superior Approach Manual Small Incision Cataract Surgery in Patients with Preoperative Against-the-Rule Astigmatism - Edmund Arthur; Ahmed Abdul Sadik; David Ben Kumah; Eugene Appenteng Osae; Felix Agyemang Mireku; Frank Yeboah Asiedu; Reynolds Kwame Ablordeppey (Journal of Ophthalmology)
The aim of the study was to report postoperative corneal and surgically induced astigmatism (SIA) in patients with preoperative against-the-rule (ATR) astigmatism who underwent superior approach manual small incision cataract surgery (MSICS). 58 eyes of 58 cataract patients with preoperative ATR astigmatism were involved in this study. All patients had operable cataracts and underwent superior approach MSICS. Keratometric (K) readings were taken prior to surgery and at 12 weeks after surgery. Centroid values of SIA, preoperative astigmatism, and postoperative astigmatism were calculated using Cartesian coordinates based analysis. Wilcoxon signed rank test was used to compute statistical significance between mean preoperative and postoperative corneal astigmatism. Cohen’s d was used as effect size measure. Centroid values of 1.42 D × 179, 2.48 D × 0, and 1.07 D × 1 were recorded, respectively, for preoperative astigmatism, postoperative astigmatism, and SIA. Wilcoxon signed rank test indicated that mean ± SD postoperative corneal astigmatism (2.80±1.40 D) was statistically significantly greater than preoperative corneal astigmatism (1.49±1.34 D), Z=-6.263, p<0.0001. A high Cohen’s d of 1.32 was found. Our results suggest statistical and clinically significant greater postoperative corneal astigmatism than preoperative corneal astigmatism for ATR astigmatism cataract patients who underwent superior approach MSICS.